EVALUATION OF EFFICACY OF PROPHYLACTICALLY USED PREMEDICATION FOR THE MANAGEMENT OF NAUSEA, VOMITING AND HYPERSENSITIVITY REACTIONS TO CISPLATIN, TAXANES AND FAC (5-FLUOROURACIL, ADRIAMYCIN (DOXORUBICIN) AND CYCLOPHOSPHAMIDE) BASED CHEMOTHERAPY: - Shireen Bhurgri; Shaneela Khowaja; Syed Mubashir Shah; Narendar Kumar; Bilal Mustafa; Danish Patoli; Rehana Arisar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
To assess pre medication’s efficacy for managing nausea, vomiting and hypersensitivity reactions before chemotherapy. An observational prospective study was conducted at Nuclear Institute of Medicine and Radiotherapy Hospital Jamshoro, Sindh, Pakistan, from November 2020 to July 2022. The study included 180 patients, aged 18-60 years. A validated questionnaire was used to record data of patients. Most frequent reaction was Tachycardia 40% in Cisplatin, 46% in Paclitaxel and 50% in Docetaxel, Hypotension 30% in Cisplatin, 40% in Paclitaxel and 5-Flouro Uracil (5-FU) and 43% in Docetaxel, Phlebitis 44% in Paclitaxel, Flushing 57% in Docetaxel, Skin rash 57% in Paclitaxel and 63% in Docetaxel, Oral sore 40% in 5-FU, Diarrhea 40% in Cisplatin, 54% in Paclitaxel, 63% in Docetaxel while 54% in Cyclophosphamide and Doxorubicin and 40% in 5-FU. Nausea, vomiting and hypersensitivity reactions were controlled significantly by the use of premedication in Cisplatin and FAC based chemotherapy while in taxane-based chemotherapy these reactions were observed in moderate range.